2015
DOI: 10.1007/s40256-014-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pump Thrombosis in Patients with Left Ventricular Assist Devices

Abstract: The gradual evolution of left ventricular assist device (LVAD) therapy has resulted in a durable option for patients as either a bridge to transplantation (BTT) or a destination therapy (DT). Outcomes with current continuous-flow devices continue to demonstrate significant patient benefit, not only in enhanced survival but also in improved functional capacity and quality of life. While the lessening of adverse events through time has resulted in more widespread adoption of this therapy, there continues to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…MT generally includes unfractionated heparin with or without the addition of glycoprotein IIb/IIIA inhibitors and thrombolytics. However, Stulak et al reported that even successful MT was associated with a high morbidity rate, including stroke ranging from 10 to 15%, bleeding complications in 65% of patients, and mortality ranging from 17 to 52% . Moreover, several series of studies have reported good outcomes following DE to treat device thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT generally includes unfractionated heparin with or without the addition of glycoprotein IIb/IIIA inhibitors and thrombolytics. However, Stulak et al reported that even successful MT was associated with a high morbidity rate, including stroke ranging from 10 to 15%, bleeding complications in 65% of patients, and mortality ranging from 17 to 52% . Moreover, several series of studies have reported good outcomes following DE to treat device thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, device thrombosis may complicate LVAD therapy and is associated with cerebrovascular events and an increased risk of mortality . While a number of investigators reported about LVAD thrombosis and treatments, a consensus has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…Rates vary in the literature but range from 5.5% to 12% . Diagnosis of early thrombosis can be subtle, but 4 early signs are pump power elevation, a rise in LDH, evidence of hemolysis, or new heart failure symptoms . A rise in LDH is a sensitive and early sign of pump thrombosis .…”
Section: Clinical Hematologic Manifestationsmentioning
confidence: 99%
“…A novel approach uses a low‐dose infusion of a bolus of 3 mg and then a 5‐ to 6‐hour infusion of t‐PA at 3 mg/h . However, the results of medical therapy are poor, with studies showing only 23% to 50% success and high rates of complications: 10% to 15% stroke, 65% bleeding, and 17% to 52% mortality . Data for surgical replacement are better, with only 0% to 6.5% early mortality, making this the therapy of choice.…”
Section: Management Strategiesmentioning
confidence: 99%
“…[83][84][85][86][87] Device thrombosis around the atrial struts in the AbioCor ® IRH was a major complication resulting in stroke and device modification. Pump thrombosis is a major fatal complication that has an average incidence of 2% to 11% in patients with HeartMate II ® (Thoratec Corporation, Pleasanton, CA) LVADs.…”
Section: Hematologic Concernsmentioning
confidence: 99%